Analysis of the Relationship between Young Marriage and Cervical Cancer Incidence - Natalia, Flora; Reva, Inara Aulia Reva (International Journal on ObGyn and Health Sciences, 2024)
This research investigates the relationship between young marriage and cervical cancer incidence, focusing on how early marital age influences reproductive health outcomes. Utilizing a retrospective cohort design, the study analyzes medical records and health registries of women aged 25 to 65 years in regions where early marriage is prevalent. The findings reveal that women who marry before the age of 18 face a significantly higher risk of developing cervical cancer, attributed to early sexual activity and childbearing, which increase exposure to high-risk human papillomavirus (HPV) infections. Socioeconomic factors and access to healthcare services, including HPV vaccination and cervical cancer screenings, are identified as critical mediators of this relationship. The research highlights the importance of culturally sensitive public health interventions aimed at delaying marriage, promoting reproductive health education, and improving access to preventive services. These findings underscore the need for targeted policies that address the unique challenges faced by young married women, ultimately contributing to the reduction of cervical cancer incidence and the promotion of women's health globally.